Building Information Modeling using Revit for Architects and Engineers - Makhmalbaf, Atefe; Open Textbook Library (Minneapolis, MN Open Textbook Library, 2022)
This book offers a web-based multimedia platform to enable students in Architecture, Civil Engineering, and Construction Engineering to learn fundamentals of BIM using Revit and be able to create building architectural, mechanical and structural models, develop construction documentation and analyze building performance. The platform include: book chapters on detailed Revit instructions and videos.
About the Publisher -- Accessibility Statement -- About This Project -- Acknowledgments -- Chapter 1: Revit Interface -- Chapter 2: Walls, Curtain Walls, Windows and Doors -- Chapter 3: Floors, Roofs and Ceilings -- Chapter 4: Stairs, Railings and Ramps -- Chapter 5: Adding- Modifying Families -- Chapter 6: Massing- Conceptual Mass -- Chapter 7: Model In-Place -- Chapter 8: Schematic Design and Room & Color Fill Plans -- Chapter 9: Materials, Visualization and Rendering -- Chapter 10: Details and Annotations -- Chapter 11: Workflow -- Worksharing -- Chapter 12: Schedules and Project Phasing -- Chapter 13: Drawing Sets and Construction Documents -- Chapter 14: Site Modelings -- Chapter 15: MEP- Fire Protection and Fabrication Parts -- Chapter 16: Structural Systems -- Links by Chapter -- Errata and Versioning History -- Accessibility Rubric
In English.
Description based on print resource
Keywords: Civil Engineering -- Textbooks; Engineering and Technology -- Textbooks